Thin-skinned and thick-skinned tear faults in central Tarim Basin - Qing Bian; Zhendong Wang; Bo Zhou; Fei Ning (Journal of Asian Earth Sciences: X, 2023)
Currently, the interpretation scheme for strike slip faults in the central Tarim Basin does not typically take into account the depth of tear faults. This paper specifically explores this aspect, focusing on two tear faults (Nos. 4 and 7) to examine the thick-skinned and thin-skinned systems in the area. By utilizing high-resolution seismic data, we discovered that No. 4 Fault is a thick-skinned tear fault whereas No. 7 Fault is a thin-skinned tear fault. Additionally, we have calculated the strata shortening data for both Nos. 4 and 7 Faults to further our understanding of these systems. For No. 4 Fault, we observed shortening differences between the western and eastern sections in both the supra- and sub-salt strata, whereas for No. 7 Fault, we observed shortening differences only in the supra-salt strata. We demonstrated that under the action of thrusting, a tear fault could penetrate the salt layer if there is a shortening difference in the different positions of the sub-salt strata. A lack of shortening difference in the sub-salt strata implies that a tear fault should be thin-skinned which cannot penetrate the salt layer, even though the sub-salt strata may be deformed during thrusting.